Maturation of dendritic cells by bacterial immunomodulators - Spisek, Radek; Brazova, Jitka; Rozkova, Daniela; Zapletalova, Katerina; Sediva, Anna; Bartunkova, Jirina (Vaccine, 2004)
Dendritic cells (DC) become fully functional upon maturation by various stimuli. We tested whether an immunostimulatory effect of clinically used immunomodulators (Luivac, Biostim, Ribomunyl, Imudon, Bronchovaxom) is caused by direct DC activation. We found that Luivac, Biostim and Ribomunyl have a very high DC stimulatory potential in vitro. The level of DC activation was comparable or higher than DC maturation induced by standard maturation stimuli, Poly (I:C) or lipopolysaccharide. Treated DC had activated phenotype, reduced phagocytic activity and they induced the proliferation of allogeneic T lymphocytes. These results are important for understanding the physiology of action of these widely prescribed agents. Administration of bacterial immunomodulators should be considered with care to avoid the potential risk of inducing an autoimmune disease. They could also be used as well-defined maturating agents in the protocols used for the ex vivo production of DC-based vaccines for clinical trials.
Keywords: antigeny povrchové; Phenotype; Cytokines; průtoková cytometrie; interleukin-10; fluorescein-5-isothiokyanát; Dendritic Cells; Adjuvants, Immunologic; chemická stimulace; dendritické buňky; Antibody Formation; Interleukin-12; Reproducibility of Results; cytokiny; lidé; Flow Cytometry; tvorba protilátek; test smíšené lymfocytární kultury; Fluorescein-5-isothiocyanate; Dextrans; Culture Media; dextrany; kultivované buňky; T-lymfocyty; Interleukin-10; endocytóza; Lymphocyte Culture Test, Mixed; Cells, Cultured; reprodukovatelnost výsledků; kultivační média; Bacteria; interleukin-12; fagocytóza; Stimulation, Chemical; Phagocytosis; Endocytosis; fenotyp; T-Lymphocytes; Antigens, Surface; adjuvancia imunologická; Humans